Acceptability, Feasibility, and Preliminary Efficacy of Schools Championing Safe South Africa, a Social Norms Intervention to Prevent HIV Risk Behavior and Perpetration of Intimate Partner Violence Among Teenage Boys. - Kuo, Caroline; Harrison, Abigail; Orchowski, Lindsay M.; Sikweyiya, Yandisa; Berkowitz, Alan; Adrian, Haley; Gana, Nandipha; Rasmeni, Akhona; McClinton Appollis, Tracy; Nevhungoni, Portia; Mathews, Catherine (AIDS & Behavior, 2025)
Schools Championing Safe South Africa is an intervention to prevent sexual violence perpetration and HIV/STI risk behavior among teenage boys, focusing on correcting misperceived social norms regarding risk behavior and engaging boys, teachers and peers in school. We tested its acceptability, feasibility, and preliminary efficacy in a pilot RCT (N = 282). 99% of intervention boys reported high satisfaction with content, format, and delivery. There was good facilitator fidelity to the manualized protocol and 99% retention at 6-month follow-up. Among intervention boys, completed acts of any sexual violence perpetration (touching, oral, anal, and/or vaginal sex) decreased from 71% (95% CI: 61%, 80%) at baseline to 55% (95% CI: 44%, 66%) at 1 month follow-up, with a percentage difference of 15% (95% CI: 4%, 26%; p = 0.004). At 6 months, change was not significant (72–68%; p = 0.353). For the intervention group, attempted acts of any sexual violence perpetration reduced from 49% (95% CI: 40%, 58%) at baseline to 25% (95% CI: 17%, 33%) at 1 month, with a percentage difference of 22% (95% CI: 11%, 32%; p < 0.001) but was not sustained at 6 months (47–43%; p = 0.446). Across timepoints, the control group did not show significant changes in completed or attempted perpetration. There were no significant changes in condom use in the intervention or control groups. Behavioral signals of positive change for prevention of sexual violence perpetration combined with high acceptability and feasibility indicate that the intervention should be tested further for efficacy.